PERMAINAN DALAM PERHITUNGAN PERKALIAN BERBASIS ONLINE MENGGUNAKAN FLASH - Khairil, Khairil; Kanedi, Indra; yono, Hari Aspri (Jurnal Media Infotama, 2012)
This research is to design an online game based on calculations using Macromedia Flash 8.0so as to help children around the world in online learning multiplication . With the website ofthis multiplication game that people can easily access games multiplication calculations quicklywithout requiring a lot of time .The research method used is the System Development Method . Information obtained by the manual will be developed in the direction of Computerized through the website so that peoplecan directly see and play the online multiplication calculations . The game was implemented to hire a Linux -based Hosting and Domain so that the website can more quickly access and security can be guaranteed .Based on the results of testing the system in the calculation of Multiplication Based GamesOnline Using Flash can assist users in learning multiplication calculations .